LANGUAGE ASSESSMENT: CONTROLLING TERRITORIES, NORMALIZING SUBJECTS - Oliveira, Diego Fernando de [UNESP] (Centro Univ Uniabeu, 2023)
Language assessment is widely employed as a tool to control access to different territories, especially in terms of international mobility. This paper aims to analyze the assessment criteria from the holistic scale of the Celpe-Bras exam in order bring into evidence the alignment of Brazilian language policies to foreign normalizing language policies. Through the use of Performance Decision Trees, this research enabled the observation of the progressive penalization of foreignness in language performances. This occurs even in cases where proficiency remains unaffected, aligning with foreign language policies like those outlined in the Common European Framework. This paper aims to foster discussions about the adoption of normalizing assessment practices in Brazil as means for regulating access to territories and influencing the (re)construction of identities for foreigners and migrants within the confines of national borders.
Keywords: Language assessment; Celpe-Bras; normalization; territory; foreignness.